Law in war : a concise overview. - Corn, Geoffrey S.; Watkin, Kenneth; Williamson, Jamie (Jamie A.) (Abingdon, Oxon ; New York, NY : Routledge, 2023)
The Law in War offers an insightful roadmap to understanding a broad range of operational, humanitarian, and accountability issues that arise during armed conflict. Each chapter provides a clear and comprehensive explanation of the impact that international law has on military operations. The second edition has been fully revised to reflect recent advances in international humanitarian law and expands the analysis to include as a brand-new chapter on international human rights law, which addresses issues such as the conduct of law enforcement during hostilities. With a particular focus on updates concerning the status of combatants and unprivileged belligerents, the protection of civilians, targeting, the treatment of POWs and detainees, weapons law, air and missile warfare, naval warfare and neutrality, command responsibility, and accountability. New material has also been added to address the increasing involvement of private security contractors in warfare.The Law in War is an ideal text for students in a variety of domains, to include international humanitarian law, international human rights law, international relations, and military science. It is also a valuable resource for those involved in the planning, execution, and critique of military operations across the spectrum of conflict.
Keywords: War (International law); Humanitarian law; War victims -- Legal status, laws, etc; Prisoners of war -- Legal status, laws, etc; Detention of persons; War crimes; LAW / General; LAW / Military